EFEKTIVITAS PENYULUHAN HUKUM OLEH LEMBAGA BANTUAN HUKUM KEADILAN JUNJUNGAN BENGKALIS DALAM MENINGKATKAN KESADARAN HUKUM MASYARAKAT - Heri; M. Nurhadi Pangestu; Rahmad Syah Imam Mustaqim; Ahmad Shirotol (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Legal awareness is an important element in realizing a law-abiding society and ensuring access to justice for all citizens. One of the efforts to increase public legal awareness is through legal counseling programs conducted by Legal Aid Institutions. This study aims to analyze the effectiveness of legal counseling conducted by the Legal Aid Institution of Keadilan Junjungan Bengkalis (LBH KNJB) in improving community legal awareness. This research employed a qualitative descriptive approach using observation, interviews, documentation, and literature studies. The findings indicate that legal counseling activities carried out by LBH KNJB have contributed positively to increasing public understanding of legal rights and obligations. The institution actively provides legal education through community outreach, legal consultation, client assistance, and legal awareness campaigns. Supporting factors include institutional commitment, government cooperation, and community participation. However, several obstacles remain, such as limited resources, uneven dissemination of legal information, and varying educational backgrounds of participants. The study concludes that legal counseling conducted by LBH KNJB is relatively effective in promoting legal awareness and expanding access to justice among the community.